Tree collections of Auckland : biodiversity and management : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Landscape Management at Massey University, Palmerston North, New Zealand - Cliffin, Penelope Frances (Massey University, 2001)
Recent developments in New Zealand environmental legislation and government policies are based on an economic world-view where landscape is portrayed as a 'natural' resource. This paradigm largely ignores the human-made urban landscape where the highest proportion of population live. Our national legislation pays little attention to urban vegetation in general and exotic tree collections in particular. Research therefore has a vital role in highlighting the character and values of urban vegetation, and in analysing the current models used to manage its continued existence. This study examines the importance of charting and managing biodiversity and focuses on managed amenity and scientific tree collections in the Auckland region. This regional study seeks to characterise the biodiversity of tree collections in Auckland, and describe how landscape management can best contribute to their biological and human-use values. The literature review establishes the importance and values of trees and urban vegetation as critical to the fabric of human lifestyles and the ecology of the city. It then reviews the basis for the preservation of biodiversity in managed plant collections. Management principles and systems are reviewed along with the legislative context in Auckland. No mandate is established for exotic plant collection managment under the Resource Management Act, 1991 (RMA1991). Management of this resource is found to lack the focus and funding from which natural and rural biodiversity benefit under the RMA and other national legislation. A biodiversity survey of thirty-eight collections of trees characterises the biodiversity in the collections, and a survey of twelve tree collection managers provides data about the goals, practices and tools used in the management of those collections. Results reveal the diverse and unique flora of Auckland tree collections, and establish a baseline for comparison over time. The regional mix of native and exotic species found in Auckland collections is compared with other national plant surveys, and demonstrates differences consistent with regional climatic character and a differing research focus. The largest collection of trees and the most specialist genera collections were found at the Auckland Regional Botanic Garden, while the university of Auckland provides the most extensive range of scientific plant-collection facilities. There is evidence of sequential open space acquisition for tree collections in the Auckland region. Comparison of best management practices put forward in current literature with current practices of collection managers in Auckland reveals some significant issues. There is little evidence found to suggest strategic plant acquisition goal setting. It is also of concern that only half the collection managers used computerised plant record systems such as inventories and specialised database systems. Only one third of the managers had management plans, and therefore documented collection goals. There was no significant difference in the use of best management practices between the private and publicly owned collections. Well-managed collections are characterised by high or specialist tree species diversity, clear strategic goal setting and management planning, computerised plant record systems, adequate resources, appropriate staffing and the use of monitoring tools. Discussion of these research results leads to three recommendations. Firstly, the management of specific sites is discussed in light of a proposed model for plant collection management. Secondly, management policy for the regional urban Forest is recommended. Lastly, the finding that Auckland's exotic tree collections are a valuable resource worthy of protection, currently having little status under the law, leads to the recommendation for the empowering of a national body (central agency) with a mandate for the national coordination of botanic gardens and plant collections. This research therefore charts aspects of Auckland's urban biodiversity with reference to current legislation and management models. Its findings and recommendations are of importance to reviewers of national environmental legislation, regional policymakers and tree collection managers.
Appendix 1: Personal Communications Contact List. Page 182 has been removed. Please consult the print copy held in the Library.
Keywords: New Zealand Auckland; Biodiversity conservation; Management; Landscape protection; Trees in cities; Protection